Techniques for In Vitro Fertilisation of Vitrified Cattle Oocytes: Challenges and New Developments - Mahlatsana Ramaesela Ledwaba; Hester Adri O’Neill; Mamonene Angelinah Thema; Ayanda Maqhashu; Masindi Lottus Mphaphathi (Agriculture)
Cryopreservation is currently an essential technique in reproductive technologies that is used for the extended preservation of genetic material. Vitrification has become the industry’s standard cryopreservation technique for cattle oocytes and embryos. The current results of this technology, however, are still not good in terms of viability, fertilisation capacity, embryo development, or pregnancy. The oocytes’ susceptibility to freezing is associated with significant changes in the structures, functioning of the oocytes, and cryoinjury, which is harmful to the survival of cells and their subsequent growth. The effectiveness of producing embryos with in vitro techniques utilising vitrified cattle oocytes rarely exceeds 30–40%. A significant number of vitrified oocytes do not successfully develop into the embryo stage following in vitro fertilisation and culture. This review focuses on issues related to oocyte cryopreservation, ways to overcome them, and how to enhance the vitrified oocyte fertilisation process.